Assessment of Additional Milk Yield and Prices in Different Seasons among Various Categories of Farmers - , Satendra Kumar, P.K. Upadhyay, Ramjee Gupta, M.Ps. Yadav, Deepak Singh, Narendra Kumar, Hari Shanker, Swashankh Kumar (Archives of Current Research International, 2025)
The present experiment is conducted to study about the additional milk yield and prices in different seasons among various categories of farmers. The study period is consisting of five different seasons (Viz. summer, rainy, autumn, winter and spring) of the year (2019-2021). Buffaloes are randomly selected from ten villages covering five blocks of district Lakhimpur (kheri). Each block contains two villages and from each village 25 farmers based on size of land holding capacity viz. Landless farmers (landless), Marginal Farmers (< 1.00 hectare), Small Farmers (1.00-2.00 hectare), Medium Famers (2.00-4.00 hectare) and Large Farmers (4.00- 10.00 hectare) were selected. In second phase improved feeding using mineral supplement 50 gm., 25 gm. Urea, 40gm. Chalk and common salt requirement for animal. The indicated order of lactation not vary significantly and stage of lactation data indicated was recorded highly significant variation (P<0.05) among various farm catogeries On perusal of data and also significant (P<.05) variation in data was analysis of additional input price, additional milk yield, and additional net profit among various farmer categories were found. Average mean data represent order of lactation was 2.84 ± 1.044, 2.64 ± 0.89, 2.60± 0.97, 2.63± 0.98 and 2.75 ± 0.96 respectively, in summer, rainy, autumn, winter and spring season under and different categories of farmers. Average mean data represent stage of lactation was 2.66± 0.73, 2.75± 0.71, 2.74 ± 0.76, 2.35 ± 0.74 and2.73± 0.75 respectively, in summer, rainy, autumn, winter and spring season and different categories of farmers. Additional input price (paise) average mean data were recorded was 56.50± 2.9, 54.84 ± 2.60, 54.92± 4.93, 57.07± 2.75 and 55.62 ± 3.58 respectively, in summer, rainy, autumn, winter and spring season and different categories of farmers. Additional milk yield (gram) average mean data were recorded as 450.20 ± 4.59,501.2 ± 8.59, 450 ± 5.98, 511.2± 8.05 and 462.2 ± 7.97 respectively, in summer, rainy, autumn, winter and spring season and different categories of farmers. Additional net profit (paise) average mean data were recorded as 393.50± 4.81, 410.34 ± 8.80, 395.12 ± 7.04, 454.34 ± 8.56 and 406.65± 8.98 respectively, in summer, rainy, autumn, winter and spring season and deferent categories of farmers.